Microbiota and depressive disorders – a review - Kosyra, Kamila; Drabczyk, Marta; Marczyńska, Zuzanna; Zyśk, Antoni; Magda, Inga (Journal of Education, Health and Sport, 2024)
Introduction: Depression, affecting 1 in 8 individuals with a 27.6% rise during COVID-19, prompts an exploration of the gut-brain-microbiota axis's role in mental health, focusing on depression. State of Knowledge: The gut microbiota regulates the brain-gut axis, impacting neurotransmitter production. Dysbiosis correlates with depressive behaviors. Factors like short-chain fatty acids and neurotrophins play roles in gut-brain communication. Materials and method: A literature review was conducted using the “PubMed” and “Google Scholar” databases with the keywords “Gut microbiota”, “Fecal microbiota”, “Depression and microbiota”, “Depression”, „Probiotics role”, „Mental health and priobiotics”, „Probiotics and prebiotics”, „Prebiotics and brain”. Summary: Altered gut microbiota links to psychiatric disorders, disrupting composition stability by age three through antibiotic use. Imbalances impact neurotransmitters and inflammation, crucial in depression pathophysiology. Treatment and Impact on Gut Microbiota: Antidepressants affect gut microbiota diversity bidirectionally, offering potential tailored therapies. The Mediterranean diet correlates with lower depression risk. Excessive sugar intake triggers neuroinflammation. Fecal Microbiota Transplantation: FMT emerges as a promising depression treatment, reshaping gut microbiota and modulating the gut-brain axis. Lactobacillus and Bifidobacterium spp. show potential in mitigating depression symptoms. FOS and GOS positively influence gut microbiota. Conclusion: This review underscores the intricate gut-brain-microbiota axis in depression, suggesting personalized therapeutic approaches for effective management.